2015
DOI: 10.3109/15368378.2015.1036076
|View full text |Cite
|
Sign up to set email alerts
|

Diseases caused by defects of energy level and loss of coherence in living cells

Abstract: Human and animal diseases are brought about by pathological alterations of production, composition, and conformation of macromolecules and structures in cells. Additional contributing factors include changes in physiological states caused by disturbances of energy supply, energy transduction, energy dissipation in moving or oscillating parts, and parasitic energy consumption. Disturbances of energy states may endanger existence of the system. The cell-mediated immunity (CMI) response of T lymphocytes correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…If the parasitic consumption exceeds a critical rate, cellular death may occur instead of cancer transformation. Cell-mediated immune response to the LDH virus antigen in patients with myocardial infarction supports the idea [44]. Our model is based on experimental data to a significant extent.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…If the parasitic consumption exceeds a critical rate, cellular death may occur instead of cancer transformation. Cell-mediated immune response to the LDH virus antigen in patients with myocardial infarction supports the idea [44]. Our model is based on experimental data to a significant extent.…”
Section: Discussionsupporting
confidence: 70%
“…If the parasitic consumption exceeds a critical rate, cellular death may occur instead of cancer transformation. Cell-mediated immune response to the LDH virus antigen in patients with myocardial infarction supports the idea [44]. The decisive part of the cancer transformation pathway is caused by biophysical mechanisms connected with damping by electrons in a Warburg effect cancer cell, in fibroblasts associated with a reverse Warburg effect cancer cell, and with short-circuiting by filaments contaminating a cell, dividing cancers into three basic phenotype groups.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The involvement of LDH virus activity in cancer origin has been confirmed by measurements of CMI response of T lymphocytes from cancer patients to the AV antigen. Similar CMI responses have been found in immunological examination in women who had suffered from recurrent spontaneous abortions in early pregnancy without having apparent gynaecological reasons, and also women who had given birth to stillborn babies, having severe organ malformations revealed on dissection (Mejsnarov a et al 1981, Jandov a et al 2015.…”
Section: Discussionsupporting
confidence: 59%
“…As living systems takes in energy in order to store and utilize information, so effectively using free energy to do work to create a highly ordered state that becomes more efficient and selectable by natural selection, it exports disorder, so maintaining the second law of thermodynamics. Panel ( A ) Proven and predicted quantum effects in biology from the literature: (1) life evolved because of, and has incorporated basic quantum principles, such as entanglement and tunnelling [40,74]; (2) aromatic compounds, such as tryptophan, have pi electrons that can delocalize, and can enable quantum effects [75]; (3) the first real evidence for quantum effects has come from the reliance of photosynthesis on electron tunnelling [41,42]; (4) natural selection appears to have resulted in macromolecules tuned for quantum effects suggesting universal mechanisms of charge transport in living matter [52,57]; (5) quantum beating has been detected in living systems, in particular, in photosystems, suggesting life is using quantum effects [41,43,46]; (6) over 40 years ago Fröhlich predicted that vibrational modes within proteins could condense leading to macroscopic coherence, this appears to have now been observed [55]; (7) tunnelling is now thought to be essential in both enzyme reactions and energy transfer, a quintessential component of the quantum world [4751,64,76]; (8) bacteria live in colonies, often sharing electrons with different species, and it seems that electrons are ‘transported’ over long distances–it would be surprising if tunnelling was not involved, and this sharing between archaea and bacteria is suggestive of this process being adopted in eukaryotes [47,7779]; (9) several groups now think that electron tunnelling is important in the ETC [4850]; (10) an important component of electron tunnelling is the existence of super-complexes–these now appear to exist in all orders of life, and are key in both photosynthesis and respiration [8082]; (11) ion channels play a key role in the brain, and it has been suggested that ion conduction could be described using quantum principles [65,66]; (12) alterations in electric fields surrounding the mitochondrion could play a significant role in changing ‘water order’ and be associated with disease states [56,83,84]; (13) long discussed theory that microtubules could be involved in resonant energy transfer and consciousness due to their quantum properties [45,75]; (14) the nuclear spin properties of phosphorous utilized by transfer of quantum entangled pairs across the synapse in Posner molecules, so effectively acting as a ‘qubit’ [85]. Panel ( B ) Some predictions of our own: (1) coherence could be controlled by mitochondrial potential, which is turn could enhance quantum tunnelling of electrons (as well, as possibly, other coherence-dependent functions, such as enzyme function or ion channel status)–it could be biphasic as it could enhance efficiency (high ATP, low ROS), but if too high, i...…”
Section: The Quantum Mitochondrionmentioning
confidence: 99%